Habituation-Based Pancasila Education: A Case Study of Grade 3 Students in Boarding School Al Fattah Bulungcangkring Jekulo - Atqiya, Muhammad Hudatil; Mubarok, Husni (Lentera : Jurnal Kajian Bidang Pendidikan dan Pembelajaran, 2025)
Pancasila Education by habituation-based in madrasah elementary schools or Madrasah Ibtidaiyah (MI) remains underexplored, its integration with formal schools. This study aims to: (1) describe the implementation of Pancasila Education for third-grade students at MI Al-Fattah Bulungcangkring; (2) identify instilling Pancasila values instilling Pancasila values through patterns of habituation model; and (3) explore an integrative habituation model.  Method that used in this study is qualitative case study design was employed, with data from in-depth interviews with one homeroom teacher, one religious lesson teacher, one caregiever and one ustaz, classroom observations of 15 students with focusing on learning methods, interests, behavior and readiness, and document analysis. Data were thematically analyzed with Mile and Hubberman aprroach. The results show that Pancasila values were internalized through organic integration of classroom lessons with pesantren habits, including routine shalat berjamaah, communal dhuha prayer, queuing for meals and ablutions, and collaborative muslim tasks. The Integrated Conceptual Habituation Model emerged as a identified framework, showing cognitive-affective reinforcement from school synergizing with behavioral domains in pesantren routines. The model offers relevant reference  contribution to character education in habituation-based. Future research should validate it via quasi-experimental designs and standardized tools like Child Behavior Checklist.